Resistance characteristics of culture-positive tuberculosis from 2015 to 2022 - Wang, Zhenzhen; Xu, Liyang; Guo, Tengfei; Li, Long; Zhang, Qing; Liu, Jinwei; Zu, Xiangyang; Zhao, Zhanqin; Xue, Yun (Frontiers in Public Health, 2025)
IntroductionThis study aimed to investigate the prevalence of resistance to first-line anti-tuberculosis (TB) drugs and the molecular mechanisms underlying resistance mutations in patients with culture-positive Mycobacterium tuberculosis complex (MTBC). The findings provide a data basis for developing more precise and regionally tailored anti-TB treatment regimens.MethodsFrom 2015 to 2022, a total of 3,605 strains isolated from 10 designated TB medical institutions in the main urban and county/township areas of Luoyang City, China, were confirmed as MTBC members through polymerase chain reaction (PCR) targeting a specific insertion sequence IS6110. Drug susceptibility testing using the proportional method was performed to analyze resistance patterns to first-line anti-TB drugs, namely, isoniazid (INH), rifampin (RFP), streptomycin (SM), and ethambutol (EMB). Molecular drug susceptibility testing was conducted on resistant strains using multicolor melting curve analysis (MMCA) to determine the mutation mechanisms associated with phenotypic resistance.ResultsAmong the 3,605 culture-positive MTBC cases, 79.5% (2,866 cases) were male, 64.9% (2,341 cases) resided in county and township areas, and 64.8% (2,336 cases) were younger than 60 years. The resistance rates for first-line anti-TB drugs, from highest to lowest, were SM (16.5%), INH (15.7%), RFP (9.9%), and EMB (6.4%). The overall TB resistance rates were significantly higher in the main urban areas. During the study period, the proportion of mono-resistance tuberculosis (MR-TB), multidrug-resistant tuberculosis (MDR-TB) and polydrug-resistant tuberculosis (PDR-TB) decreased by 59.2% (12.9–5.3%), 40.3% (12.4–7.4%), and 68.3% (6.9–2.2%), respectively. The predominant resistance patterns for MDR-TB and PDR-TB were MDR4 (INH + RIF + EMB + SM) and PDR2 (INH + SM). The significant molecular mutations observed were rpsL43 for SM resistance (66.2%, 344 cases), katG315 for INH resistance (70.6%, 361 cases), rpoB529-533 for RFP resistance (54.0%, 183 cases), and embB306 for EMB resistance (56.5%, 108 cases). Resistance in MDR-TB and PDR-TB cases frequently involved combinations of hotspot mutations but was not strictly confined to these sites.ConclusionTuberculosis resistance rates have declined over time, with distinct regional variations in resistance patterns. Significant molecular mutations responsible for drug resistance predominantly involve common hotspot mutations, but they are not limited to these.